Effects of protein diet on expression of Anoctamin1 of Cajal cell in the nervous plexus of the stomach in male mice - Khulood Ayad Majeed; Haider Abdal-Rasool Jaafar; Hiba Majed Rasol (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the association between a protein-rich diet and the expression of anoctamin 1 in Interstitial cells of Cajal within the muscle layer of the stomach wall in male mice. Method: The experimental study was conducted at the Anatomy Department of the College of Medicine, Al- Nahrain University, Iraq, from November 2020 to April 2021, and comprised male adult healthy male mice. They were divided randomly into two equal groups. Group A was fed a high protein diet, while control group B was fed a standard pellet diet. The tissue samples were harvested at day 30 post-surgery. The stomach samplings were placed in 10% neutral formalin for 24 hours to obtain paraffin sections for routine histological and immunohistochemical staining. The protein expression in stomach smooth muscle of each group was detected by immunohistochemical staining. Data was analysed using SPSS 24. Result: Of the 20 mice, 10(50%) were in each of the two groups. Group A exhibited significant weight-gain compared to group B (p less than or equal to 0.05). There was significant elevation in muscle wall thickness in group A, compared to group B (p less than or equal to 0.05). Tunica muscularis of the stomach in group A significantly thickened compared to group B (p less than or equal to 0.05). The expression of anoctamin 1 was significantly more intense in group A compared to group B (p less than or equal to 0.01). Conclusion: Unbalanced food had a significant impact on the stomach, affecting the thickness of the muscularis layer and the expression of anoctamin 1 in cajal cells in the muscularis externa. Key Words: Anoctamin, Paraffin, Cajal, Formaldehyde